Replik til Hans J. Lundager Jensens "De fremmede, Det Gamle Testamente, vi" - Andersen, Vagn (Religionsvidenskabeligt Tidsskrift, 1987)
The article is a reply to the foregoing article by Hans Jørgen Lundager Jensen and discusses especially HJLJ’s concept of cultural identity. It is held, that HJLJ’s concept of identity in the final analysis implicates a Nietzsche-inspired idea of identity as powerful self-assertion. In contrast to this, a Hegel-inspired idea of identity as mutual recognition is advanced. Taken in this manner, the reply is a variation on the philosophical objections raised by Jürgen Habermas against Michel Foucault. In consequence, a cosmopolitical version of cultural identity is sketched and some of its problems are discussed.